E-library utilization among students of Tai Solarin University of Education, Ogun State, Nigeria (2014)
The study reveals that e-resources such as e-books, e-journals, e- magazines/newspapers, e-databases are available in the e- library for the students' use. It revealed e- magazines/newspapers as always used by students of Tai Solarin University of Education (TASUED), with e-journals occasionally used. Persistent power failure, lack of access to e- library, and limited bandwidth were the major constraints hindering students' effective use of e-resources in the e-library. Students' internet self-efficacy was found to have a significant influence on the perceived usefulness and perceived ease of use of e-library among the students while perceived usefulness and perceived ease of use were found to positively influence e-library usage among the students.